Outside the Box: (Post) Secular Projects of Transcendence. Issue 4 (December 2015) - Cady, Linell
Abstract: Secular theology builds upon the growing recognition and critique of the limitations of the confining box of religion built in and through the modern secularist dispensation. A bipolar model of religion and the secular, and the classificatory web within which it is nestled, have limited theology's field of vision and engagement. This article explores several examples of projects of transcendence that resist easy identification with either the religious or the secular, illuminating the limitations of the religion‐secular classification and the diffuse cultural trends that are reconfiguring it, even leading beyond it.